Ekspresi Nilai dalam Praktik Wisata Budaya Bejango Bliq di Desa Songak Kabupaten Lombok Timur - Pauzi, Muh. Hilmi; Junaidi, Muhammad Adi (LPPM Institut Pendidikan Nusantara Global, 2025)
This study aims to identify and analyze the values contained in the implementation of cultural tourism in Songak Village, particularly in the Bejango Bliq tradition, as well as to examine and explore how the practice of cultural tourism is carried out in the village. This research provides information and understanding that the implementation of cultural tourism in Songak Village utilizes traditional elements as the main driving force in fulfilling tourism attractions. The results of the study indicate that field findings reveal various values embedded in the Bejango Bliq tradition in Songak Village, including religious values, norms of politeness and etiquette, social and kinship values, cultural and customary values, as well as economic values. Furthermore, the practice of cultural tourism in Songak Village has been established and sustained over generations, as it has been passed down from ancestors and is now part of the official tourism event calendar in East Lombok Regency. Prior to the Bejango Bliq cultural tourism event, various other activities are also organized, including traditional ceremonies and other ceremonial events.